Method for preparing aluminum fluoride and lithium hydroxide by using lithium-containing aluminum electrolyte
By employing a method that includes ball milling, calcination, leaching, and bipolar membrane electrodialysis, the method addresses the inefficiencies and environmental issues in aluminum electrolyte processing, achieving efficient recovery of aluminum fluoride and lithium hydroxide with reduced by-product generation and energy use.
Patent Information
- Application Number
- CN202411332240.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2024-12-17
AI Technical Summary
The accumulation of alkali metal impurities in aluminum electrolyte during electrolytic aluminum production leads to decreased primary crystallization temperature, reduced current efficiency, increased energy consumption, and generates hazardous fluoride waste, necessitating a more efficient and environmentally friendly method for resource utilization.
A method involving mixing lithium-aluminum electrolyte with aluminum sulfate, ball milling, high-temperature calcination, leaching with water, bipolar membrane electrodialysis, and nanofiltration to produce aluminum fluoride and lithium hydroxide without producing additional by-products or consuming large amounts of auxiliary materials.
This method effectively recovers valuable materials while reducing environmental impact and operational costs by eliminating the need for sodium sulfate by-products and minimizing energy consumption.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of aluminum electrolyte resource utilization, and in particular to a method for preparing aluminum fluoride and lithium hydroxide by using lithium-containing aluminum electrolyte. Background Art
[0002] In the process of electrolytic aluminum production, as the alumina raw materials are consumed, alkali metal impurities such as Li, Na, and K, which are more electronegative than Al, continue to accumulate in the aluminum electrolyte, resulting in a decrease in the primary crystallization temperature of the aluminum electrolyte melt and a decrease in the ability to dissolve the alumina raw materials, which leads to difficulties in the operation of the electrolytic cell, reduced current efficiency, and increased energy consumption. In order to maintain the normal operation of electrolytic production, it is necessary to continuously remove alkali metal-rich aluminum electrolyte from the aluminum electrolytic cell, and 10-15 kg of fluoride electrolyte waste slag is generated for every ton of raw aluminum produced. Aluminum electrolyte waste slag contains a large amount of fluoride, which poses a risk of fluorine pollution spread and is a large amount of hazardous waste that needs to be treated urgently.
[0003] At present, the resource utilization process of aluminum electrolyte is mainly: aluminum electrolyte is leached with aluminum chloride aqueous solution, lithium is extracted in the form of lithium chloride, and the final product is lithium salt, and the byproducts are cryolite and sodium chloride. Chinese patent application CN114804171A discloses a method for preparing aluminum fluoride and lithium carbonate using lithium-containing aluminum electrolyte, the lithium-containing aluminum electrolyte is pre-crushed, the crushed material is mixed with aluminum sulfate, the obtained mixture is ground to obtain powder A; the powder A is pressed into a mass or loaded into a crucible for compaction, the mass or the crucible containing powder A is placed in a high-temperature furnace for roasting, and after roasting, a clinker B is obtained; clinker B is leached with water, filtered after leaching, and filtrate C and filter cake D are obtained, and filter cake D is washed and dried to obtain aluminum fluoride; sodium carbonate solution is added to filtrate C for reaction, and a suspension is obtained after the reaction, and the suspension is subjected to solid-liquid separation to obtain precipitate E and solution F; precipitate E is washed and dried to obtain product lithium carbonate; solution F is evaporated and crystallized to recover sodium sulfate.
[0004] This method uses the traditional sodium carbonate lithium precipitation process to recover lithium salts, so a large amount of sodium sulfate will be produced as a by-product, increasing the cost of resource recovery of aluminum electrolytes. Summary of the invention
[0005] The object of the present invention is to provide a greener method for preparing aluminum fluoride and lithium hydroxide using a lithium-aluminum electrolyte.
[0006] The method for preparing aluminum fluoride and lithium hydroxide using a lithium-aluminum electrolyte provided by the present invention comprises the following steps: S1: mixing the lithium aluminum electrolyte and aluminum sulfate, grinding them into powder by ball milling, and calcining them at a high temperature of 450-700°C; S2: adding water to the powder obtained by calcining in step S1 for leaching, filtering the leached solution obtained after leaching to obtain a filtrate containing lithium sulfate and a filter cake; removing impurities from the filter cake to obtain aluminum fluoride; S3: removing impurities from the filtrate containing lithium sulfate obtained in step S2, freezing it to precipitate sodium sulfate crystals, and filtering and removing the precipitated sodium sulfate crystals; S4: The filtrate from which sodium sulfate has been removed is subjected to bipolar membrane electrodialysis to obtain a lithium hydroxide solution and a sulfuric acid solution.
[0007] Bipolar membrane is a special membrane technology, which consists of an anion exchange layer and a cation exchange layer, with an extremely thin intermediate layer between the two layers. Bipolar membrane has a unique property that can dissociate water into hydrogen ions (H ⁺ ) and hydroxide ions (OH ⁻ ), and can simultaneously separate and convert ions. The lithium sulfate solution is converted into lithium hydroxide solution and sulfuric acid solution by bipolar membrane electrodialysis, which does not consume a large amount of auxiliary material sodium carbonate, nor does it produce additional by-product sodium sulfate.
[0008] Furthermore, in the step S1, the particle size D50 of the powder of the mixture after ball milling is controlled to be 25-30 μm.
[0009] Furthermore, in step S2, the mass ratio of the added water to the powder is 4 to 3:1.
[0010] Add water for leaching and filtration. The main components of the filter cake are aluminum fluoride, and a small amount of sodium sulfate and aluminum sulfate; the main components of the filtrate are lithium sulfate and sodium sulfate solution, and a small amount of fluoride ions and aluminum ions.
[0011] Furthermore, in step S2, the process of removing impurities from the filter cake is as follows: a dilute sulfuric acid solution is mixed with the filter cake to form a slurry, the slurry is ball-milled, deionized water is added to dilute the slurry, and the slurry is filtered; and the filter cake is washed with deionized water to obtain purified aluminum fluoride.
[0012] Furthermore, in step S2, the pH of the dilute sulfuric acid is 2 to 3, and the mass ratio of the dilute sulfuric acid to the filter cake is 2 to 3:1 to prepare the slurry.
[0013] Dilute sulfuric acid is added to remove insoluble impurities in the obtained aluminum fluoride, and the obtained aluminum fluoride is further purified by washing with deionized water.
[0014] Furthermore, in step S3, the operation of removing impurities from the filtrate containing lithium sulfate is: adding an impurity remover to the filtrate containing lithium sulfate to remove fluoride ions and aluminum ions; the impurity remover is selected from at least one of sodium carbonate, liquid alkali, lime, modified polyaluminum sulfate, and modified basic zirconium sulfate.
[0015] The impurities in the filtrate containing lithium sulfate are mainly fluoride ions, aluminum ions, and a small amount of calcium ions and magnesium ions. Therefore, fluoride is removed by lime, modified polyaluminum sulfate, and modified basic zirconium sulfate, and then calcium ions and magnesium ions are removed by liquid alkali and sodium carbonate.
[0016] Lime (Ca(OH)2) can remove fluoride ions (F ⁻ ). This method is usually called lime precipitation. Lime reacts with fluoride ions to form insoluble calcium fluoride precipitate (CaF2), thereby removing fluoride ions. The reaction equation is as follows: Ca 2+ +2F − →CaF2↓.
[0017] Modified polyaluminium sulfate and modified basic zirconium sulfate can both be used as effective fluoride ion removers. These modified materials remove fluoride ions from water by adsorption, precipitation and other methods.
[0018] Modified polyaluminium sulfate is usually modified by adding different modifiers (such as organic or inorganic substances) to change its surface properties to improve the adsorption capacity of fluoride ions. The aluminum ions in polyaluminium sulfate can form a stable complex with fluoride ions, thereby adsorbing fluoride ions. The modified polyaluminium sulfate is added to fluoride-containing water in a certain proportion, and the contact and reaction between fluoride ions and polyaluminium sulfate are promoted by stirring. Fluoride ions react with polyaluminium sulfate to form a precipitate, which can be removed by precipitation or filtration.
[0019] Modified basic zirconium sulfate changes its surface charge state or increases active sites by adding specific modifiers to improve its adsorption capacity for fluoride ions. The zirconium ions in basic zirconium sulfate can form stable complexes with fluoride ions, thereby adsorbing fluoride ions. Modified basic zirconium sulfate is added to fluoride-containing water in a certain proportion, and the contact and reaction between fluoride ions and basic zirconium sulfate are promoted by stirring. Fluoride ions react with basic zirconium sulfate to form a precipitate, which can be removed by precipitation or filtration.
[0020] Furthermore, in step S3, the filtrate after removing impurities is concentrated to 0.15 to 0.25 of the original volume, and then frozen at a temperature of -4 to -6°C.
[0021] Furthermore, in step S3, the precipitated sodium sulfate decahydrate crystals are dissolved in deionized water, and then evaporated and crystallized to finally obtain anhydrous sodium sulfate.
[0022] Furthermore, in step S4, the obtained lithium hydroxide solution is subjected to nanofiltration to remove impurities.
[0023] Nanofiltration is a membrane separation technology between reverse osmosis and ultrafiltration. Nanofiltration devices are mainly used to remove impurities such as divalent and multivalent ions, small molecular organic matter, color, taste and odor from water. Compared with reverse osmosis, nanofiltration has a lower operating pressure, while compared with ultrafiltration, nanofiltration has a better desalination capacity. The pore size of nanofiltration membranes is generally around 1 nanometer (nm) and can retain solutes with a molecular weight between 200-1000 Da. Nanofiltration membranes usually have a certain charge, which makes them effective in removing charged particles such as divalent and multivalent ions.
[0024] Furthermore, in step S4, the lithium hydroxide solution after nanofiltration is subjected to evaporation and crystallization to obtain lithium hydroxide crystals.
[0025] Battery-grade lithium hydroxide can be produced through the above purification technology.
[0026] The present invention discloses a method for preparing aluminum fluoride and lithium hydroxide using a lithium-aluminum electrolyte, wherein the lithium-aluminum electrolyte and aluminum sulfate are mixed, ball-milled, and then calcined at high temperature, and then filtered to separate solid aluminum fluoride and a solution containing lithium sulfate after water immersion, and then the solution containing lithium sulfate is frozen to remove sodium sulfate in the filtrate, and then converted into lithium hydroxide and sulfuric acid through bipolar membrane electrodialysis. It does not require the use of a large amount of other auxiliary materials, and does not produce additional by-products, which is more economical and more energy-saving and emission-reducing. DETAILED DESCRIPTION
[0027] In order to make the technical solution of the present invention clearer, the present invention is further described in detail below in conjunction with specific embodiments.
[0028] Example 1
[0029] The aluminum-lithium electrolyte to be treated is subjected to elemental analysis: The element contents in the lithium-aluminum electrolyte are: Li 1.83%, Na 24%, K 1.5%, Fe 0.20%, Al 8.34%, Ca 2.0%, and F 51.5%.
[0030] The specific processing steps are as follows: S1: Weigh 50.0g of aluminum electrolyte and 150.0g of aluminum sulfate and divide them equally into four planetary ball mills. Mill for 1h. The D50 of the obtained powder is 30.20μm (the inner wall of the ball mill is made of polyurethane material). Place the powder obtained after grinding and mixing in a muffle furnace, calcine at 610℃ for 45min, and cool to room temperature.
[0031] S2: The mixture obtained after calcination was mixed with deionized water in a 1000mL beaker at a mass ratio of 1:3, and stirred for 1h, and then filtered using a vacuum pump to obtain 430mL of filtrate (whose main components are lithium sulfate, sodium sulfate, and a small amount of aluminum sulfate) and 49g of filter cake (whose main components are aluminum fluoride, which contains sodium sulfate and aluminum sulfate). The obtained filter cake was prepared into a slurry with a dilute sulfuric acid solution of about pH 2.5 and the filter cake at a mass ratio of 2:1. The slurry was ball-milled for 30 min and then taken out, and the slurry was diluted with deionized water at a mass ratio of 1:1, and then vacuum filtered, and the obtained filter cake was washed with a little deionized water and dried to obtain 37g of purified aluminum fluoride.
[0032] S3: performing chemical analysis on the filtrate containing lithium sulfate obtained in step S2; The concentrations of cations in the filtrate containing lithium sulfate are: Li 1.9 g / L, Na 26.8 g / L, Ca 2.3 g / L.
[0033] The 10L filtrate containing lithium sulfate was concentrated to 2L. According to the results of the chemical analysis, sodium carbonate and modified basic zirconium sulfate (chemical formula: ZrOSO4·nH2O) were added to remove impurities. The filtrate containing lithium sulfate and sodium sulfate and the filter residue containing the main components of sodium sulfate and calcium carbonate were obtained by filtration. The filtrate after impurity removal was placed in a low-temperature constant temperature water bath (ethylene glycol antifreeze was added to the cold circulating water) for freezing crystallization. The temperature was set to -5°C, and sodium sulfate decahydrate crystals and lithium sulfate solution were obtained by filtration.
[0034] The obtained sodium sulfate decahydrate crystals are dissolved in deionized water, evaporated and crystallized in a rotary evaporator, and finally anhydrous sodium sulfate (sodium sulfate) is obtained.
[0035] The obtained lithium sulfate solution was subjected to chemical analysis: The concentrations of lithium ions and sodium ions in the lithium sulfate solution are: Li 9.5g / L, Na 1.0g / L.
[0036] S4: The obtained lithium sulfate solution is introduced into a bipolar membrane system EX-3BT type experimental device to prepare a lithium hydroxide solution and a dilute sulfuric acid solution.
[0037] 100 L of the obtained lithium hydroxide solution is subjected to nanofiltration and impurity removal on a small nanofiltration device to obtain a lithium hydroxide solution after impurities are removed; 5 L of the lithium hydroxide solution after impurities are taken and evaporated and crystallized on a rotary evaporator to obtain lithium hydroxide crystals; The aluminum fluoride, anhydrous sodium sulfate (sodium sulfate) and lithium hydroxide crystals obtained in step S2, step S3 and step S4 are sent for analysis.
[0038] After laboratory analysis: Aluminum fluoride: F 60.1%, Al 31.1%, Na 0.55%, SiO2 0.30%, Fe2O3 0.01%, SO4 2- 0.53%, P2O5 0.003%, caustic soda content 1.7%, bulk density 1.2g / cm 3 .
[0039] Anhydrous sodium sulfate: sodium sulfate 99.5%, water insoluble matter 0.04%, calcium and magnesium 0.005%, chloride 0.07%, water 0.07%, whiteness 82%.
[0040] Lithium hydroxide crystals: LiOH 56.7%, Na 0.0030%, K 0.0020%, Ca 0.0015%, Cu 0.0000%, SO4 2- 0.0050%, acid insoluble matter 0.0030%.
[0041] Aluminum fluoride meets the requirements of GB / T 4292-2017 AF-2, anhydrous sodium sulfate meets the requirements of Class I superior products of GB 6009-92, and lithium hydroxide crystals meet the requirements of GB / T 26008-2020.
[0042] Example 2
[0043] The aluminum-lithium electrolyte to be treated is subjected to elemental analysis: The element content in the lithium-aluminum electrolyte is: Li 1.83%, Na 24%, K 1.5%, Fe 0.20%, Al8.34%, Ca 2.0%, and F 51.5%.
[0044] The specific processing steps are as follows: S1: Weigh 50.0g of aluminum electrolyte and 150.0g of aluminum sulfate and divide them equally into four planetary ball mills. Mill for 1h. The D50 of the obtained powder is 28μm (the inner wall of the ball mill is made of polyurethane material). Place the powder obtained after grinding and mixing in a muffle furnace, calcine at 650℃ for 40min, and cool to room temperature.
[0045] S2: The mixture obtained after calcination was mixed with deionized water in a 1000 mL beaker at a mass ratio of 1:4, and stirred for 1 hour, and then filtered using a vacuum pump to obtain 570 mL of filtrate (whose main components are lithium sulfate, sodium sulfate, and a small amount of aluminum sulfate) and 49 g of filter cake (whose main components are aluminum fluoride, which contains sodium sulfate and aluminum sulfate). The obtained filter cake was prepared into a slurry with a dilute sulfuric acid solution of about pH 2.5 and the filter cake at a mass ratio of 2:1. The slurry was ball-milled for 30 min and then taken out, and the slurry was diluted with deionized water at a mass ratio of 1:1, and then vacuum filtered, and the obtained filter cake was washed with a little deionized water and dried to obtain 37 g of purified aluminum fluoride.
[0046] S3: performing chemical analysis on the filtrate containing lithium sulfate obtained in step S2; The concentrations of cations in the filtrate containing lithium sulfate are: Li 1.43 g / L, Na 20.1 g / L, Ca 1.73 g / L.
[0047] 10L of filtrate containing lithium sulfate is concentrated to 2L, and impurities are removed with sodium carbonate and modified polyaluminum sulfate (the trade name is polyaluminum silicate sulfate), and filtered to obtain a filtrate containing lithium sulfate and sodium sulfate and a filter residue containing sodium sulfate and calcium carbonate as the main components. The impurity-removed filtrate is placed in a low-temperature constant temperature water bath (ethylene glycol antifreeze is added to the cold circulating water) for freezing and crystallization, the temperature is set to -5°C, and sodium sulfate decahydrate crystals and lithium sulfate solution are obtained by filtration.
[0048] The obtained sodium sulfate decahydrate crystals are dissolved in deionized water, evaporated and crystallized in a rotary evaporator, and finally anhydrous sodium sulfate (sodium sulfate) is obtained.
[0049] The obtained lithium sulfate solution was subjected to chemical analysis: The concentrations of lithium ions and sodium ions in the lithium sulfate solution are: Li 9.6g / L, Na 1.1g / L.
[0050] S4: The obtained lithium sulfate solution is introduced into a bipolar membrane system EX-3BT type experimental device to prepare a lithium hydroxide solution and a dilute sulfuric acid solution.
[0051] 100 L of the obtained lithium hydroxide solution is subjected to nanofiltration and impurity removal on a small nanofiltration device to obtain a lithium hydroxide solution after impurities are removed; 5 L of the lithium hydroxide solution after impurities are taken and evaporated and crystallized on a rotary evaporator to obtain lithium hydroxide crystals; The aluminum fluoride, anhydrous sodium sulfate (sodium sulfate) and lithium hydroxide crystals obtained in step S2, step S3 and step S4 are sent for analysis.
[0052] After laboratory analysis: Aluminum fluoride: F 60.2%, Al 31.0%, Na 0.53%, SiO2 0.33%, Fe2O3 0.015%, SO4 2- 0.52%, P2O5 0.002%, caustic soda content 1.6%, bulk density 1.23g / cm 3 .
[0053] Anhydrous sodium sulfate: sodium sulfate 99.6%, water insoluble matter 0.03%, calcium and magnesium 0.004%, chloride 0.06%, water 0.05%, whiteness 83%.
[0054] Lithium hydroxide crystals: LiOH 56.8%, Na 0.0033%, K 0.0025%, Ca 0.0018%, Cu 0.0000%, SO4 2- 0.0060%, acid insoluble matter 0.0040%.
[0055] Aluminum fluoride meets the requirements of GB / T 4292-2017 AF-2, anhydrous sodium sulfate meets the requirements of Class I superior products of GB 6009-92, and lithium hydroxide crystals meet the requirements of GB / T 26008-2020.
[0056] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing aluminum fluoride and lithium hydroxide using a lithium-aluminum electrolyte, characterized in that: The following steps are involved: S1: mixing the lithium aluminum electrolyte and aluminum sulfate, grinding them into powder by ball milling, and calcining them at a high temperature of 450-700°C; S2: adding water to the powder obtained by calcining in step S1 for leaching, filtering the leached solution obtained after leaching to obtain a filtrate containing lithium sulfate and a filter cake; removing impurities from the filter cake to obtain aluminum fluoride; S3: removing impurities from the filtrate containing lithium sulfate obtained in step S2, freezing it to precipitate sodium sulfate crystals, and filtering and removing the precipitated sodium sulfate crystals; S4: The filtrate from which sodium sulfate has been removed is subjected to bipolar membrane electrodialysis to obtain a lithium hydroxide solution and a sulfuric acid solution.
2. The method for preparing aluminum fluoride and lithium hydroxide using a lithium-aluminum electrolyte according to claim 1, characterized in that: In the step S1, the particle size D50 of the powder of the mixture after ball milling is controlled to be 25-30 μm.
3. The method for preparing aluminum fluoride and lithium hydroxide using a lithium-aluminum electrolyte according to claim 1, characterized in that: In the step S2, the mass ratio of the added water to the powder is 4 to 3:
1.
4. The method for preparing aluminum fluoride and lithium hydroxide using a lithium-aluminum electrolyte according to claim 1, characterized in that: In step S2, the process of removing impurities from the filter cake is as follows: mixing the filter cake with a dilute sulfuric acid solution to form a slurry, ball-milling the slurry, adding deionized water to dilute the slurry and filtering; washing the filter cake with deionized water to obtain purified aluminum fluoride.
5. The method for preparing aluminum fluoride and lithium hydroxide using a lithium-aluminum electrolyte according to claim 4, characterized in that: In step S2, the pH of the dilute sulfuric acid is 2-3, and the mass ratio of the dilute sulfuric acid to the filter cake is 2-3:1 to prepare a slurry.
6. The method for preparing aluminum fluoride and lithium hydroxide using a lithium-aluminum electrolyte according to claim 1, characterized in that: In step S3, the operation of removing impurities from the filtrate containing lithium sulfate is as follows: adding an impurity remover to the filtrate containing lithium sulfate to remove fluoride ions and aluminum ions; the impurity remover is selected from at least one of sodium carbonate, liquid alkali, lime, modified polyaluminum sulfate, and modified basic zirconium sulfate.
7. The method for preparing aluminum fluoride and lithium hydroxide using a lithium-aluminum electrolyte according to claim 1, characterized in that: In the step S3, the filtrate after removing impurities is concentrated to 0.15 to 0.25 of the original volume, and then frozen at a temperature of -4 to -6°C.
8. The method for preparing aluminum fluoride and lithium hydroxide using a lithium-aluminum electrolyte according to claim 7, characterized in that: In the step S3, the precipitated sodium sulfate decahydrate crystals are dissolved in deionized water, and then evaporated and crystallized to finally obtain anhydrous sodium sulfate.
9. The method for preparing aluminum fluoride and lithium hydroxide using a lithium-aluminum electrolyte according to claim 1, characterized in that: In step S4, the obtained lithium hydroxide solution is subjected to nanofiltration to remove impurities.
10. The method for preparing aluminum fluoride and lithium hydroxide using a lithium-aluminum electrolyte according to claim 9, characterized in that: In the step S4, the lithium hydroxide solution after nanofiltration is subjected to evaporation and crystallization to obtain lithium hydroxide crystals.
Citation Information
Cited By
Method for preparing regenerated aluminum fluoride from aluminum electrolysis fluorine-containing solid waste
CN121181013A
